CHARACTERIZATION OF ANTIBACTERIAL SUBSTANCEPRODUCED BY Pseudomonas Fluorescens - Waleed, Sinai (Iraqi Journal of Science, 2024)
Pseudomonas fluorescens isolate was isolated from soil. The antibacterial activity of crude extract of this isolate was determined against pathogenic bacteria (Klebsiella pneumonia, Staphylococcus aureus) which are isolated from patients with skin infections. The extraction of this substance was done and study it characterization after purified by silica gel chromatography, It was stable within range of pH (5-9) at 37 ºC for 24 hr. and inactivated by serum at concentration > 50%. The substance was soluble in methylene chloride, chloroform, acetone, sodium hydroxide and hydrochloric acid and it was insoluble in water, methanol, ethyl acetate and hexane.